Saying it right, doing it wrong : an analysis of the failure of the African Union’s mediation in Darfur (2004-2006) - Igba, Samuel Ajogwu (University of Pretoria, 2023)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2022.